Distribution of dissolved Fe, Al and Cu at Perhentian Island, Terengganu - Godon, Edrianna; Mohamed, Khairul Nizam (UKM, 2016)
Concentrations of dissolved Fe, Al and Cu were studied in seawater profile collected from Perhentian Island, Terengganu in two different seasons; during pre-monsoon in October 2014 and during post-monsoon in April 2015. Surface concentrations ranged from 227.36±1.72μg/L to 1014±9.09 μg/L (pre) and 292.38±2.84 μg/L to 546.89±5.38 μg/L (post) for Fe, 16.65±0.19 μg/L to 46.39±0.66 μg/L (pre) and 95.32±0.01 μg/L to 259.98±0.04 μg/L (post) for Al and as for Cu, its concentration was from 1.14±0.01 μg/L to 2.81±0.01 μg/L (pre) and 1.73±0.01 μg/L to 4.00±0.04 μg/L (post). Meanwhile the concentrations for dissolved metals during October 2014 were in the range of 80.80±0.71 μg/L to 1014.28±9.09 μg/L for Fe, 9.94±0.11 μg/L to 238.22±2.22 μg/L for Al, and 0.81±0.01 μg/L to 2.81±0.01 μg/L for Cu respectively. In April 2015, dissolved Fe concentrations was in the range of 167.20±1.59 μg/L to 546.89±5.38 μg/L, meanwhile for Al was between 60.97±0.03 μg/L to 259.98±0.04 μg/L and for Cu was 1.73±0.01 μg/L to 5.81±0.05 μg/L. This study suggested the increasing concentration of these dissolved metal during post monsoon event was a result from rapid mixing and strong turbulence of water current during the season.